Prediction Model Financial Distress (Bankruptcy) On The Company PT. Garuda Indonesia (Persero) Tbk With Model Altman, Springate, Zwijewski, Fullmer And Taffler - Larasati, Inggrit; Audra Nailufar (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
This investigate points to distinguish a liquidation show to foresee the condition of the PT company. Garuda Indonesia will involvement liquidation within the future. The models utilized in this inquire about are Altman Z-Score, Springate, Zwijewski, Fullmer and Taffler. The result of this demonstrate is to be able to decide whether the company is sound or on the skirt of insolvency. The information utilized in this investigate is the company PT Garuda Indonesia with yearly budgetary reports for the period 2019, 2020, 2021 and 2022. From the Expectation Comes about Investigation table for PT Garuda Indonesia (Persero) Tbk, 2019-2020, it can be seen that the normal esteem The normal of each budgetary trouble strategy appears that PT Garuda Indonesia (Persero) Tbk is declared to be within the destitute budgetary category and is in peril of going bankrupt, be that as it may agreeing to the Taffler strategy PT Garuda Indonesia, Tbk is within the Gray Zone, to be specific a company that's having monetary challenges In any case, the plausibility of being spared and the plausibility of going bankrupt similarly depends on the choice of the company administration as the choice creator.